1998
DOI: 10.1074/jbc.273.46.30669
|View full text |Cite
|
Sign up to set email alerts
|

Betaine-homocysteine Methyltransferase Is a Developmentally Regulated Enzyme Crystallin in Rhesus Monkey Lens

Abstract: We describe herein the characterization of a major 45-kDa protein from the soluble ␤H-crystallin fraction of rhesus monkey (Macaca mulatta) lens. Based on partial peptide sequence, immunoreactivity, and enzymatic activity, this protein has been identified as betaine-homocysteine S-methyltransferase (BHMT: EC 2.1.1.5), an enzyme that catalyzes the methylation of homocysteine using either betaine or thetins as methyl donors. This protein was found to be expressed abundantly in the nuclear region of the monkey le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 39 publications
1
41
0
Order By: Relevance
“…The overall fold of the subunit can be observed in Figure 2(a) and consists mostly of an (a/b) 8 barrel with additional units of secondary structure inserted between the a/b (residues 10-318), an extended arm including residues 319 -370 and mainly involved in dimerization contacts, a flexible linker from 371 to 380, and a long a-helix including residues 381-406. From the inspection of the initial electron-density maps, it became obvious that the orientation of this C-terminal helix was different in the four subunits.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall fold of the subunit can be observed in Figure 2(a) and consists mostly of an (a/b) 8 barrel with additional units of secondary structure inserted between the a/b (residues 10-318), an extended arm including residues 319 -370 and mainly involved in dimerization contacts, a flexible linker from 371 to 380, and a long a-helix including residues 381-406. From the inspection of the initial electron-density maps, it became obvious that the orientation of this C-terminal helix was different in the four subunits.…”
Section: Resultsmentioning
confidence: 99%
“…The BHMT reaction has been shown to occur mainly in liver and kidney, where the enzyme has been localized by immunohistochemistry, 7 but its apparition in lens has also been reported in Rhesus monkey. 8 BHMT has been identified associated to tubulin in microtubules 9 and linked to autophagosomes. 10 Moreover, it has recently been shown that 0022-2836/$ -see front matter q 2004 Elsevier Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…This enzyme is found mainly in the liver and kidney of mammals. A developmentally regulated BHMT is also expressed in the lens of rhesus monkeys and humans (25). BHMT is fairly abundant in the liver and represents 0.5-1.6% of the total soluble protein in the mammalian liver (8).…”
mentioning
confidence: 99%
“…There are no reports indicating that the catalytic efficiency of BHMT is regulated by phosphorylation, but this possibility cannot be eliminated at this time. Furthermore, there is one report that used Western analysis to detect BHMT following two-dimensional electrophoresis of protein extract made from monkey lenses, which suggested that BHMT is subject to posttranslational modification (23). This report did not characterize the modification(s) to BHMT or whether the modified form(s) differed in terms of its catalytic efficiency.…”
Section: Discussionmentioning
confidence: 79%
“…BHMT expression in the kidney of humans and pigs has been shown to be limited to the proximal tubules of the cortex (6). Notable exceptions to the general rule that BHMT is a liver and kidney enzyme include the high expression of this protein in the lenses of rhesus monkeys (23) and in the pancreas of sheep (31).…”
mentioning
confidence: 99%